Does carbohydrate supplementation enhance tennis match play performance? - Vitasovic Gomes, R.; Dario Capitani, C.; Ugrinowitsch, C.; Zourdos, M. C.; Fernandez-Fernandez, J.; Mendez-Villanueva, A.; Saldanha Aoki, M. (Journal of the International Society of Sports Nutrition, 2013)
Background: Carbohydrate (CHO) ingestion may be an interesting approach to avoid significant decrement to the tennis match performance. The aim of the present investigation was to assess the effects of CHO supplementation on tennis match play performance. Methods: Twelve young tennis players (18.0 ± 1.0 years; 176 ± 3.4 cm; 68.0 ± 2.3 kg; body fat: 13.7 ± 2.4%) with national rankings among the top 50 in Brazil agreed to participate in this study, which utilized a randomized, crossover, double blind research design. The experiment was conducted over a 5-day period in which each player completed two simulated tennis matches of a 3-hour duration. The players received either a CHO or a placebo (PLA) drinking solution during simulated tennis matches. Athlete`s performance parameters were determined by filming each match with two video cameras. Each player was individually tracked for the entire duration of the match to measure the following variables: (1) games won; (2) rally duration; (3) strokes per rally; (4) effective playing time (%); (5) aces; (6) double faults; (7) first service in; (8) second service in; (9) first return in and (10) second return in. Results: There were no differences between trials in any of the variables analyzed. Conclusions: CHO supplementation did not improve tennis match play performance under the present experimental conditions.